PENGARUH UKURAN PERUSAHAAN, AUDIT TENURE, DAN FINANCIAL DISTRESS TERHADAP KUALITAS AUDIT - Fabia Syafanisa Lizara; Bambang Subiyanto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
High audit quality can build the trust of users of financial statements as a basis for decision making, both for their individual and public interests. The purpose of this research is to do a quantitative test of the effect of firm size, audit tenure, and financial distress on audit quality. The independent variable firm size is measured by the natural logarithm of total assets, audit tenure is measured by the length of the audit service engagement between the auditor and the auditee, and financial distress is measured by the debt to equity ratio. The dependent variable of audit quality is measured by a KAP reputation proxy. The data for this study amounted to 195 from 39 sample companies that published financial reports for the period 2017 – 2021 (5 years). The type of data taken is secondary data obtained from the official website of the Indonesia Stock Exchange and each company. The technique used is logistic regression analysis processed using SPSS 26. The results of this study shows that firm size and audit tenure have a significant positive effect on audit quality, while financial distress has a negative effect on audit quality.